2006
DOI: 10.1007/s10620-006-9078-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Calprotectin Levels in Patients Suffering from Acute Pancreatitis

Abstract: Calprotectin (Cal) concentration is elevated in acute inflammatory reactions and its increase in the plasma suggests a diagnostic potential for Cal assay. This study aimed (a) to evaluate the Cal plasma levels in patients suffering from acute pancreatitis (AP) and (b) to assess whether early assay of Cal plasma levels can be helpful in assessment of the severity of AP. Forty-six consecutive patients, median age 45 years, suffering from a first attack of AP were recruited at two medical centers. Data collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Plasma levels in calprotectin have been shown to increase in acute inflammation in previous studies (24,25). Calprotectin, as a promising new marker for diagnoses of inflammatory pathologies, having been detected in various body fluids, and was found to be present in gastric fluid in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…Plasma levels in calprotectin have been shown to increase in acute inflammation in previous studies (24,25). Calprotectin, as a promising new marker for diagnoses of inflammatory pathologies, having been detected in various body fluids, and was found to be present in gastric fluid in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…Subsequently, it has been recognized as a promising marker of various inflammatory disorders. High levels of S100A8 and S100A9 can be found in synovial fluid, sputum, stool, and blood plasma/serum during inflammatory diseases such as rheumatoid arthritis [40], pancreatitis [41], or hepatitis [42]. These investigations indicated that other organ insult might be also associated with elevated levels of S100A8 and S100A9, which suggested that the serum level of calprotectin might be a very sensitive nonspecific inflammatory marker in various clinical settings.…”
Section: Discussionmentioning
confidence: 95%
“…12 However, data available for patients with pancreatic diseases have been reported only for serum calprotectin as a marker of infl ammation in patients with acute pancreatitis. 13 Thus, this prospective study was designed to assess fecal calprotectin in order to evaluate the presence of intestinal infl ammation in patients with pancreatic disease.…”
Section: Introductionmentioning
confidence: 99%